1983
DOI: 10.1002/1097-0142(19830915)52:6<974::aid-cncr2820520607>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil (F), adriamycin (A), and cisplatin (P) (FAP): Combination chemotherapy of advanced esophageal carcinoma

Abstract: Twenty‐one patients with advanced epidermoid carcinoma of the esophagus were treated with a combination of 5–fluorouracil (F) 600 mg/m2 day 1 and day 8; Adriamycin (A) 30 mg/m2 day 1; and cisplatin (P) 75 mg/m2 day 1 (FAP) with hydration and mannitol‐induced diuresis. Each course was repeated every 4 weeks. All 21 patients are evaluable for response: 7 patients had an objective response (33%). Two of these responses were complete remissions according to negative endoscopic and pathologic results; five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Furthermore, combination chemotherapy with 5‐FU, ADM and CDDP (FAP) has been reported to be useful in the treatment of advanced gastric cancer, esophageal cancer and other carcinomas 7,8 . Gisselbrecht et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, combination chemotherapy with 5‐FU, ADM and CDDP (FAP) has been reported to be useful in the treatment of advanced gastric cancer, esophageal cancer and other carcinomas 7,8 . Gisselbrecht et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gisselbrecht et al . reported that the FAP regimen was administered to 21 patients with advanced esophageal cancer, 7 seven of them had an objective response (CR: 2, PR: 5), with no severe myelosuppression or nephrotoxicity observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the JCOG concluded that standard-dosage FP is superior to daily low-dosage FP [22]. Concerning the next regimen of standard FP for the neoadjuvant setting or for the non-surgical setting, several regimens such as DFC and FAP are being investigated now in Japan [23][24][25][26][27][28].…”
Section: Chemotherapy Regimenmentioning
confidence: 99%